Feeding the Enemy to the Goddess: War Magic in Śaiva Tantric Texts - Olga Serbaeva (Religions, 2022)
This article deals with the war magic as described in Sanskrit Śaiva tantric texts written between the 5th and the 12th Century A.D. This period marks a shift from the invocation of Aghora/Bhairava as the main war-helping god to the rituals invoking terrible goddesses, mātṛkās, yoginīs. At the same time, tantric religious specialists were invited to exchange their magical knowledge for kings’ patronage in such contexts as war, drought, epidemics and such. The original presupposition was that the rituals related to war shall be most violent and transgressive in the texts of the tantric initiated, compared to the Śaiva purāṇas written for broader public, and that of the “mixed” literature (that is one written by the initiated for the kings). However, this was contradicted by the text-based evidence, and it is the “mixed” literature that proposes the most violent rituals, while the whole subject of war happened to be of minor importance in the tantric literature. The war-prayogas were included to attract attention of the kings, but the aim of that was for the internal ritual use. The explanation of this contradiction is based on the fact that somewhere between the 10th and the 12th century, the tantric specialists working for the kings actually duped them into performing violent war-magic rituals, while the real intent of those procedures is actually calling the yoginīs in order to achieve a higher state in religious practice for the initiated himself. The article includes the materials from the Jayadrathayāmala and the Ṣaṭsāhasrasaṃhitā edited and translated for the first time.